PHENOMENON OF ISCHEMIC STEAL SYNDROME IN PATIENTS WITH DIFFERENT ARTERIOVENOUS FISTULAS FOR HEMODIALYSIS AND ITS SURGICAL CORRECTION - V. M. Sedov; S. A. Karpov; S. V. Alfyorov; K. M. Grinyov (Вестник хирургии имени И.И. Грекова, 2018)
Patients with arteriovenous fistulas (648 cases) were examined for hemodialysis. The ischemic steal syndrome was detected in 47 patients and it was associated with vascular access for hemodialysis. A frequency of given complication was studied with correlation of the type of vascular access. The data of clinical and instrumental examination were described. It was revealed, that the development of steal syndrome was influenced by the blood circulation volume velocity on fistulas. Different reconstructive operations were performed on 42 patients in order to save the access for hemodialysis and eliminate the ischemia. The ligation of fistula was carried out for 5 patients. The survival of arteriovenous fistulas after reconstructive operations was till 46 months during the period of follow-up study.